Mình xin sửa lại cái đề chút :
Đề : Cho [TEX]b \in N ; b > 1 [/TEX] , chứng minh rằng :
[TEX]\frac{1}{b} - \frac{1}{b+1} < \frac{1}{b^2} < \frac{1}{b-1} - \frac{1}{b}[/TEX]
Mình xin giải luôn :
Ta có :
[TEX]\frac{1}{b} - \frac{1}{b+1} = \frac{b+1}{b^2+b} - \frac{b}{b^2+b} = \frac{1}{b^2+b}[/TEX]
[TEX]\frac{1}{b-1} - \frac{1}{b} = \frac{b}{b^2-b} - \frac{b-1}{b^2-b} = \frac{1}{b^2-b}[/TEX]
Vì [TEX]\frac{1}{b^2+b} < \frac{1}{b^2} < \frac{1}{b^2-b}[/TEX]
\Rightarrow [TEX]\frac{1}{b} - \frac{1}{b+1} < \frac{1}{b^2} < \frac{1}{b-1} - \frac{1}{b}[/TEX]